Bitumen emulsions based on Ukrainian surface-active substances - Pyshyev, Serhiy; Grytsenko, Yuriy; Koval, Tetyana (Видавництво Львівської політехніки, 2013)
Bitumen emulsions can be obtained based on surface-active substances (SAS) according to DSTU B V.2.7- 129:200 produced at JSC “Barva” (Ukraine). These emulsions meet the demands of mentioned standard relative to sieve residue homogeneity, storage quality after 7 and 14 days and conventional viscosity at 25 C.
Keywords: bitumen; bitumen emulsion; surface-active substance; pavement; bilding material